Analisa Unjuk Kerja Grid Tied Inverter Terhadap Pengaruh Radiasi Matahari dan Suhu PV pada PLTS On-Grid - Nahela, Safri; Faridyan, Ivan Fauzi; Rachman, Noviadi Arief; Risdiyanto, Agus; Susanto, Bambang (ELKHA : Jurnal Teknik Elektro, 2019)
Abstract – Solar radiation and temperature in photovoltaic (PV) can affect the output voltage and current of PV so that it also relates to the performance of the Grid Tied Inverter (GTI) on the on-grid PV system. This paper discusses the performance of the GTI based on output power on solar radiation and PV temperature. The method used in this testing was measuring simultaneously against the current and voltage parameters on PV, the current and voltage of the GTI, and the radiation and temperature of PV. Measurement with a data logger was also carried out on the above parameters in the morning and evening to find out at least the PV output voltage and current when the GTI starts or stops sending the power. The measurement results obtained that the GTI output power is affected by solar radiation and PV temperature. On the same radiation when the PV temperature gets higher, the PV voltage will drop, but the PV current and GTI current will increase. In addition, if with the same radiation and temperature but the AC source voltage was greater, the output power of GTI would also increase. The power produced by the GTI was lower than PV power due to GTI losses. The efficiency of the GTI decreases not only because of the increase in temperature above 35 oC but also due to the decreasing grid voltage. GTI starts sending power when the PV current was more than 2 A at 06.23 AM. GTI stops operating when the PV current was less than 1.74 A at 05.53 PM.